Critical Parties: How Parties Evaluate the Performance of Democracies. Issue 1 (8th February 2017) - Rohrschneider, Robert; Whitefield, Stephen
Abstract : While the 'critical citizens' literature shows that publics often evaluate democracies negatively, much less is known about 'critical parties', especially mainstream ones. This article develops a model to explain empirical variation in parties' evaluations of democratic institutions, based on two mechanisms: first, that parties' regime access affects their regime support, which, secondly, is moderated by over-time habituation to democracy. Using expert surveys of all electorally significant parties in twenty-four European countries in 2008 and 2013, the results show that parties evaluate institutions positively when they have regular access to a regime, regardless of their ideology and the regime's duration. Moreover, regime duration affects stances indirectly by providing democracies with a buffer against an incumbent's electoral defeat in the most recent election. The findings point to heightened possibilities for parties to negatively evaluate democracies given the increased volatility in party systems in Europe.